Local Response to Conservation Practices in Use for the Protection of Tinau River, Nepal - Dahal, Khet Raj; Guragain, Hari Parsad (Hydro Nepal: Journal of Water, Energy and Environment, 2013)
A study was undertaken to identify the pressing problems in the Tinau River and to suggest ways to overcome the various problems such as pollution, riverbed extraction, bank erosion and threats to the foundation of bridges, etc. The study showed several problems responsible for deteriorating the health of the Tinau River. The Study suggests that the agencies and stakeholders should work together to counter the various negative problems. A Commission involving the concerned representatives from the Government, Municipality, DDC, VDC and the stakeholders such as WUAs of irrigation, water supply and others has been proposed to be established. All the river conservation practices from the Government and funding agencies have to be implemented with the active participation of the beneficiaries. It must be started as early as possible. The effective way of river conservation would be the active participation of the local inhabitants with meaningful Government support. Hydro Nepal; Journal of Water, Energy and Environment Vol. 12, 2013, January Page: 32-38 DOI: http://dx.doi.org/10.3126/hn.v12i0.9029 Uploaded Date : 10/29/2013